Coordinated variation in stem and leaf functional traits of temperate broadleaf tree species in the isohydric–anisohydric spectrum. (9th March 2021) - Chen, Zhicheng; Zhang, Yongtao; Yuan, Weijie; Zhu, Shidan; Pan, Ruihua; Wan, Xianchong; Liu, Shirong
Abstract: Stomatal regulation serves as an important strategy for plants to adapt to drought. However, the understanding of how complexes of plant-functional traits vary along the continuum from isohydry to anisohydry remains insufficient. In this study, we investigated a proxy of the degree of iso/anisohydry—the water potential at stomatal closure—and a series of functional traits of leaves and branches in 20 temperate broadleaf species planted in an arid limestone habitat in northern China. The results showed that the water potential at stomatal closure was significantly correlated with many functional traits. At the anisohydric end of the spectrum, species had a higher leaf carbon content and vein density, a greater stomatal length, a thicker lower leaf epidermis, higher embolism resistance, higher wood density, a greater Huber value, a greater ratio of fiber wall thickness to xylem lumen diameter, a larger proportion of total fiber wall area to xylem cross-sectional area, a lower water potential at the turgor loss point (TLP), a smaller relative water content at the TLP, a lower osmotic potential at full turgor and a smaller specific leaf area. It is concluded that a continuum of coordination and trade-offs among co-evolved anatomical and physiological traits gives rise to the spectrum from isohydry to anisohydry spanned by the 20 tree species, and the anisohydric species showed stronger stress resistance, with greater investment in stems and leaves than the isohydric species to maintain stomatal opening under drought conditions.